2020
DOI: 10.1007/s10592-020-01297-z
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping-by-sequencing reveals the effects of riverscape, climate and interspecific introgression on the genetic diversity and local adaptation of the endangered Mexican golden trout (Oncorhynchus chrysogaster)

Abstract: Genotyping-by-sequencing reveals the effects of riverscape, climate and interspecific introgression on the genetic diversity and local adaptation of the endangered Mexican golden trout (Oncorhynchus chrysogaster).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 115 publications
(126 reference statements)
1
4
0
Order By: Relevance
“…Effective population size (Ne), usually less than the census population size, influences genetic diversity in a population. Our results showed lower levels of Ne ranging from 0.8 to 1.2, and similar observations were reported by Escalante et al (2020) and Diaz et al (2021) . Inbreeding and genetic drift are expected to reduce genetic diversity as Ne decreases ( Frankham, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
“…Effective population size (Ne), usually less than the census population size, influences genetic diversity in a population. Our results showed lower levels of Ne ranging from 0.8 to 1.2, and similar observations were reported by Escalante et al (2020) and Diaz et al (2021) . Inbreeding and genetic drift are expected to reduce genetic diversity as Ne decreases ( Frankham, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
“…These inconsistencies may be associated with the lower number of loci analyzed in microsatellites studies when compared to SNP datasets, hence SNPs reflect genome-wide genetic diversity of populations more accurately than microsatellites 6 . The overall low genetic diversity values found for M. margaritifera are commonly found in other endangered freshwater organisms, such as Australian freshwater crocodiles and Mexican golden trout 44 , 45 and have also been estimated for North American M. margaritifera 24 and M. hembeli 26 , suggesting a strong relation between the loss of genetic diversity and the poor conservation status of these species. The low genetic diversity values found in the Iberian populations have been explained by strong genetic drift effects due to population bottlenecks 20 , 21 .…”
Section: Discussionmentioning
confidence: 93%
“…One reason for this may be that the complex geographical environment and evolutionary history of the QTP have a longlasting impact on species survival and promote species adaptation to local conditions (Mao et al, 2021;Shen et al, 2021). Studies have indicated that local adaptations may affect the genetic diversity of populations (Escalante et al, 2020;Zhao et al, 2020). For commercially exploited salt lakes (ABL, YC, and QXC) that have low genetic diversity, exploiters must consider rational exploitation.…”
Section: Discussionmentioning
confidence: 99%